Electrical braking in matrix converter for more electric aircraft: bi-directional switch and input power clamp methods - Munuswamy, Imayavaramban; Wheeler, Patrick (American Scientific Publishers, 2015)
Current aircraft power quality specifications do not allow regeneration onto the power bus. Therefore, the inherent regeneration available from Matrix Converter (MC) is not desirable in More Electric Aircraft (MEA) aerospace applications. In this paper, novel methods to avoid regeneration from the Matrix Converters are proposed. The methods have been called the Bi-Directional Switch (BDS) method and the Input Power Clamp (IPC) method. Both methods are compared. The IPC method is considered an alternative to the Bi-Directional Switch (BDS) method and has a number of advantages discussed in the paper. To detect regeneration in Matrix Converters two techniques are proposed, the Power Comparison technique (PC) and the Input Voltage Reference technique (IVR). Experimental results from a prototype using 4 kW Induction Motor are presented.